Autophagy and mitochondrial dysfunction in adjuvant-arthritis rats treatment with resveratrol - Zhang, Junqiang (Sci Rep, 2016)
Resveratrol is a polyphenol derivatives which exhibits a pro-apoptotic effect in a variety of human cancers by triggering mitochondria apoptosis pathway and autophagy. However, there are scarcely reports on its apoptosis-promoting effect in abnormal proliferation fibroblast-like synoviocytes (FLSs). In this study, we investigated the underlying mechanism and apoptosis-inducing effects of resveratrol on the abnormal proliferation of FLSs in adjuvant-arthritis (AA) rats. Since using resveratrol for 12 days resulted in a significant decreasing the swelling degree of the paw, reducing malondialdehyde (MDA) content and enhancing superoxide dismutase (SOD) activity, antioxidant capacity, glutathione peroxidase and glutathione reductase ratio in AA rats. Moreover, we found that 5 μMH(2)O(2) could increase cells viability, Beclin1, LC3A/B, MnSOD, SIRT3 protein expression in FLSs. But, resveratrol could reverse these effects by changing mitochondrial membrane potential (Δψm) to promote mitochondrial reactive oxygen species (mtROS) generation in 5 μMH(2)O(2)-treatment FLSs. These results suggest that oxidative stress existed in AA rats. Resveratrol could suppress oxidative stress in AA rats and increase mtROS production by reducing autophagy protein Beclin1, LC3A/B and oxidative stress protein MnSOD to promoted the apoptosis of FLSs. Thus, targeting of mtROS may be a crucial mechanism of resveratrol confers patients with rheumatoid arthritis.